The Plant Endoplasmic Reticulum - Robinson, David G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
The endoplasmic reticulum (ER), called "the mother of all membranes," is spotlighted in this timely new book. The work presented here is especially exciting since GFP-technology has provided new ways of looking at the dynamics of the ER and its relationship to other organelles, particularly the Golgi apparatus and peroxisomes. This book provides in-depth knowledge of the ER and the diverse roles it plays—for instance, in protein trafficking, homeostasis of cellular calcium, plant hormone and lipid synthesis. These manifold activities are reflected in the great plasticity of the ER as a structure, with more than a dozen specialized domains recognized for this organelle.
The Morphology and Dynamics of the ER -- Targeting of RNAs to ER Subdomains and its Relationship to Protein Localization -- The ER Folding Helpers: A Connection Between Protein Maturation, Stress Responses and Plant Development -- Endoplasmic Reticulum-associated Protein Degradation in Plant Cells -- ER-to-Golgi Transport: The COPII-Pathway -- Transport of Proteases to the Vacuole: ER Export Bypassing Golgi? -- Induction of Specialized Compartments from the ER -- Synthesis of Structural and Storage Lipids by the ER -- Oleosins and Endoplasmic Reticulum in Seeds and Anthers -- Participation of the Plant ER in Peroxisomal Biogenesis -- The ER and Plant Hormones -- The ER and Cell Calcium -- The ER Within Plasmodesmata -- The ER in Replication of Positive-Strand RNA Viruses.
Keywords: Cell biology; Plant physiology; Plant anatomy; Plant development; Cell Biology; Plant Physiology; Plant Anatomy/Development.